2017
DOI: 10.1159/000481651
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Airway Smooth Muscle Cell Proliferation Involves TRPC6-Dependent Calcium Influx Via α7 nAChR

Abstract: Background/Aims: The proliferation of human bronchial smooth muscle cells (HBSMCs) is a key pathophysiological component of airway remodeling in chronic obstructive pulmonary disease (COPD) for which pharmacotherapy is limited, and only slight improvements in survival have been achieved in recent decades. Cigarette smoke is a well-recognized risk factor for COPD; however, the pathogenesis of cigarette smoke-induced COPD remains incompletely understood. This study aimed to investigate the mechanisms by which ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 78 publications
6
25
0
Order By: Relevance
“…Our results on nicotine-induced death of airway epithelial cells as well as alveolar epithelial cells further support its toxic effects and are also consistent with a report on colonic epithelial cells (19). Long-term exposure to millimolar concentrations of nicotine results in a steady increase of intracellular calcium, which may also lead to cell damage (35). Taken together, these studies suggest that inhaled nicotine at doses commonly found in e-cigs can cause systemic inflammation, barrier disruption, cell death, and pulmonary edema (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our results on nicotine-induced death of airway epithelial cells as well as alveolar epithelial cells further support its toxic effects and are also consistent with a report on colonic epithelial cells (19). Long-term exposure to millimolar concentrations of nicotine results in a steady increase of intracellular calcium, which may also lead to cell damage (35). Taken together, these studies suggest that inhaled nicotine at doses commonly found in e-cigs can cause systemic inflammation, barrier disruption, cell death, and pulmonary edema (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Airway remodeling is defined as the deposition of collagen and associated structural changes in an asthmatic airway, including smooth-muscle hypertrophy and cell hyperplasia [17,18]. Because airway remodeling represents a significant social and economic burden, asthma has become an important health challenge in developed countries [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, a well-believed major component of cigarette smoking extract, has been demonstrated plays an essential role in developing enhanced airway contraction and airway smooth muscle cell proliferation. Nicotine elevated [Ca 2+ ] i in rat airway smooth muscle cells via activating and up-regulating α7 nAChR in ASMCs 33 34 . Therefore, mapping the molecular mechanisms for nicotine induced alterations in bronchial smooth muscle cells may offer clues into COPD pathogenesis and treatment.…”
Section: Discussionmentioning
confidence: 97%